Implementasi Merdeka Belajar Melalui Pusat Informasi Megalitikum Bondowoso (PIMB) sebagai Sumber Pembelajaran Sejarah - Wijanarko, Ario Setyo; Wahyudi, Deny Yudo; Sayono, Joko (PAKAR Pendidikan, 2024)
The purpose of this research is to find out the implementation of independent learning through the Bondowoso Megalithic Information Centre (PIMB) as a history learning resource. The research method used is descriptive qualitative research. Data collection using interviewers and observation. The results showed that the implementation of independent learning carried out by high schools in Bondowoso Regency in history subjects had fulfilled all elements of independent learning. The elements are teacher (educators), Students (learners), learning places, leaders, learning program and coordinastion. In addition, all learning activities that have been carried out are able to achieve the objectives of independent learning, namely stimulating the way students learn from fun media in the PIMB museum, honing students' creativity to be more sensitive to various objects seen, getting a new atmosphere and being able to coordinate with each other between group members in completing the assigned tasks, producing student output with superior quality, namely not only memorising subject matter but also having sharp analytical skills, reasoning and comprehensive understanding.